Penerapan Good Corporate Governance terhadap Kinerja Perusahaan - Dhyani Dewi, I Gusti Ayu Agung; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2023)
Company performance is a benchmark for assessing the success of management in achieving company goals. The aim of the research is to prove empirically the effect of implementing Good Corporate Governance on company performance. The research was conducted on 20 state-owned companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The selection of company samples was carried out using purposive sampling method. Company performance is measured by Return on Assets and Good Corporate Governance is measured by indicators of the board of commissioners, managerial ownership, institutional ownership and audit committees. The data analysis technique used is multiple linear regression test. The results showed that the board of commissioners, institutional ownership, and audit committees have a positive effect on company performance, while managerial ownership has a negative effect on company performance. Keywords: Company Performance; Board of Commissioners; Managerial Ownership; Institutional Ownership; Audit Committee